The interrelation of informal institutions and governance quality in shaping Welfare State attitudes - Hans Pitlik; Ludek Kouba (WWWforEurope, 2013)
This paper addresses empirically determinants of individual support for the Welfare State. We examine the interrelation of informal institutions with the perceived quality of a country's institutional framework. As a proxy for informal institutions, we concentrate on three core beliefs (trust in other people, perceived control over one's own life, and religiousness) which reflect different aspects of the way people feel about internal and external constraints in managing their own lives. To analyze preferences we follow a comprehensive concept of the Welfare State, measuring attitudes toward its two basic roles, (income) redistribution and government intervention. For this purpose the paper uses survey data from the World Values Survey/European Values Study as well as different indicators for governance quality. Our results indicate that people who interpret their life course as being not at their own disposition report a substantially more positive attitude toward income equalization and government interventions. A higher quality of public administration and low confidence in major private companies amplify preferences for redistribution and intervention of people under such an external locus of control. Social trust is generally associated with higher support for redistribution and government intervention only if perceived quality of administration is high and confidence in companies is low. People who assert themselves as religious are less favorable toward income equalization. While variation in administration quality does not appear to have an impact on the relationship between religiousness and income equalization preferences, religious people are substantially less supportive of redistribution and government intervention especially if confidence in major companies is high.
Keywords: D74; D78; P35; 330; Political economy of policy reform; welfare reform; welfare state